GENERALIZATION STRATEGY OF LINEAR PATTERNS FROM FIELD-DEPENDENT COGNITIVE STYLE - Yayan Eryk Setiawan; Purwanto Purwanto; I Nengah Parta; Sisworo Sisworo (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2020)
Linear pattern is the primary material in learning number patterns in junior high schools, but there are still many students who fail to generalize the linear pattern. The students’ failure in generalizing the pattern occurred when the students ended to view the problems globally without breaking them into the constructors’ components such as the experience of field-dependent type students. For this reason, this study was carried out to explore the thinking process of students who fail and investigate the thinking processes of students who succeed in generalizing linear patterns. The results of this study provide an effective learning strategy solution for field-dependent students in generalizing linear patterns. This study employed a qualitative approach with a case study design to junior high school students. The results indicated that students in the field-dependent cognitive style looked at pattern questions represented in the form of geometric images globally without looking at the structure of the image. Two strategies for generalizing linear patterns used by field-dependent students were examined, namely recursive and different strategies.